Traditional buffalo rears: A study of migratory Guijar in Himachal Pradesh - PATHANIA, M S; SHARMA, S K; SHARMA, K D; VASHIST, G D; KATOCH, ANUP (The Indian Journal of Animal Sciences, 2011)
Average livestock holding was 13.76 animals. Buffalo dominated livestock population. Average proportion of both stallfed as well as grazing animals was 95.70 %. By grazing, 42 to 90 % of fodder was saved for different catergories of animals. Cost of rearing a buffalo was estimated to be Rs 45639. Average income per annum per household was Rs 101133 out of which livestock rearing accounted for maximum (98%) share. There was decrease in diseases, improvement in health and increase in milk production of buffaloes on the higher hills. The maximum buffaloes and young stock were affected with foot-and-mouth disease followed by diarrhoea. The maximum mortality occurred due to diarrhoea in buffaloes. Mortality and morbidity during migration were higher in plains followed by high hills. In fact, migration was a compulsion for Gujjars due to paucity of fodder, adverse climate conditions and family traditions. Â